Low temperature below 200 °C solution processed tunable flash memory device without tunneling and blocking layer - Sandip Mondal (Nature Portfolio, 2019)
Realizing efficient non-volatile flash memories that do not require high temperature processing to create suitable charge trapping remains a challenge. Here, the authors report low-temperature solution-processed oxide-based flash memories with low leakage, tunable memory storage and good retention.